The role of oxytocin signaling in depression and suicidality in returning war veterans. (April 2021) - Warrener, Corinne D.; Valentin, Edward M.; Gallin, Camilla; Richey, Lynnet; Ross, Deanna B.; Hood, Chelsea J.; Lori, Adriana; Cubells, Joseph; Rauch, Sheila A.M.; Rilling, James K.
Abstract: Many war veterans struggle with depression and suicidality, and separation from the military is a time of particularly high risk. Based on research in non-human animals, we hypothesized that reduced oxytocin signaling would mediate symptoms of depression and suicidality in war veterans recently separated from their close comrades. We also hypothesized that veterans with more frequent contact with comrades would have fewer symptoms of depression and suicidality. In this cross-sectional study, male veterans from the Iraq and Afghanistan wars (n = 86) provided blood and urine samples for measurement of peripheral oxytocin (OT) levels, as well as saliva samples for DNA extraction followed by genotyping of oxytocin receptor gene ( OXTR ) Single Nucleotide Polymorphisms, and CpG-methylation assessment. Participants also completed a series of mental health questionnaires and interviews. Veterans reported feeling very close to their comrades during war, and missing them greatly upon returning home. Neither peripheral OT levels nor OXTR genotypes were related to symptoms of depression or suicidality. On the other hand, methylation at OXTR CpG −924 was negatively correlated with depressive symptomology, after controlling for possible confounds. Veterans who socialized with comrades more frequently had higher levels of urinary, but not plasma OT, as well as less depressive symptomology. Social connectedness was a strong negative predictor of symptoms of both depression and suicidality, eclipsing the predictive power of other variables such as post-deployment social support, the degree to which participants reported missing their comrades, and the frequency with which they socialized with comrades. Our results suggest that veteran mental health is more impacted by lack of social connectedness than by separation from close comrades per se. While there is some evidence that OXTR methylation relates to depressive symptomology, decreased OT signaling does not appear to mediate the relationship between social disconnectedness and depression or suicidality. Sleep quality and anxiety disorders were also significantly associated with mental health symptoms, independent of social connectedness. Our findings suggest that efforts aimed at alleviating the burden of depression and suicidality in returning war veterans should focus on re-integrating veterans into society and establishing a feeling of social connectedness, as well as on treating anxiety disorders and sleep problems. Highlights: War veterans report feeling very close to their comrades during war. Methylation of the oxytocin receptor gene is related to depression in war veterans. Social connectedness is negatively correlated with depression and suicidality. PTSD symptomology is positively correlated with depression in war veterans. Sleep quality is negatively correlated with depression in war veterans.